(3OjhGf GdcYHjs - (3GdMGL gGTe Hf MQOGf GdcYHj,J (B1231 (3g` s ((3eMeO Hf WGgQ GdSeGhj s)
(3ChdgG (B:s
(3gPG eG hLO ef TYQ GdTGYQ GdaMd GdMGL gGTe GdcYHj, hbO LYdJg HGHjf(B: (3GdHGH GdChd aj eOM hQKGA Cgd GdHjJ hGdJhSd Hge hGdHGH GdKGfj aj ZjQge hjONd ajg GdZRd s
(3BNQgG (B:s
(3CQi PcQkG aj bdHj hde CHQM Hg CMjG dh Cf GdPcQ Ph GSe dUjQ GSeg jMji s
(3hQO CjVkG JMJ Qbe (B2198s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B186 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs